2015
DOI: 10.4103/0972-6748.181721
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of caregivers of mentally ill patients in a tertiary care hospital

Abstract: Objectives:To explore the quality of life (QOL) and its association with psycho-sociodemographic factors among caregivers of mentally ill patients in a tertiary care hospital in urban India.Materials and Methods:Sample consisted of 100 caregivers attending outpatient services in a tertiary care hospital. Data was collected using World Health Organization QOL-BREF (WHOQOL-BREF) questionnaire. The higher score meant a better QOL.Results:Of 100 caregivers, 66% were men, 47% were parents and 64% were literate. 52%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
(18 reference statements)
0
23
1
Order By: Relevance
“…In fact, family caregivers can have an additional suffering by watching someone they love suffer. The effect of caring for a patient with a mental disorder on the quality of life (QoL) of family caregivers has been highlighted in previous reports [3,4,5,6]. The low QoL of caregivers, probably, comes from reactions to the illness, changes in the household routine, and/or a reduction in leisure activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, family caregivers can have an additional suffering by watching someone they love suffer. The effect of caring for a patient with a mental disorder on the quality of life (QoL) of family caregivers has been highlighted in previous reports [3,4,5,6]. The low QoL of caregivers, probably, comes from reactions to the illness, changes in the household routine, and/or a reduction in leisure activities [7].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with several studies in which it has reported that less educated, unemployed, female and elderly caregiver, patient's gender had statistically significant association with impaired quality of life as compare to their counterparts. 8,9,13,18,[22][23][24][25][26]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a high level of stress, headache and family conflict, were also common in caregivers of individual with mental illness. 8 It has been reported that environmental condition, caregivers' factors and caregiving situation had a significant impact on QOL of caregivers. Sociodemographic features of the patient such as age, gender, marital status, education status and patients' diagnosis had a direct link to psychosocial distress and QoL of a caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…The family caregivers were also asked to indicate the number of hours per day and the number of years during which they provided care for their family member. The number of hours per day and years of providing care have been used in several studies as objective measures for caregivers' burden among several populations, including mentally ill patients (Basheer et al, 2015), chronically ill patients (Chang et al, 2010), and Alzheimer's patients (Haro et al, 2014). In addition, in an open-ended question, we asked the family members to indicate the health condition, diagnosis, illness, or disability of their care recipient for whom they were providing care.…”
Section: Measures and Data Collectionmentioning
confidence: 99%